Research of the Transverse Vibration of Friction and Meshing Composite Transmission V Belt based on Recurdyn - Li Zhanguo; Yang Xiuguang; Wang Jinfang; Shi Yaochen (Jixie chuandong)
Aiming at the friction and meshing composite transmission V belt system,which used in a certain oilfield beam pumping,the simulation model of the V belt drive system is built based on the rigid- flexible coupled dynamics software Recurdyn,and the dynamics simulation analysis is carried out,the transmission performance is obtained. The transverse vibration of the system is analyzed by changing the speed,tension and load,and the rule of the transverse vibration of the system is got,the simulation basis for the research of friction and meshing composite transmission V belt is provided.